Print reading for engineering & manufacturing technology - Madsen, David A.; Madsen, David P. (Delmar/Cengage Learning, 2013)
Takes a practical approach to print reading, with fundamental through advanced coverage that demonstrates industry standards essential for pursuing careers in the 21st century